Leveraging blockchain for enhanced social and environmental accountability: a conceptual framework - Safeei, Roshidah; Abu Hassan, Nor Asni Syahriza (Universiti Teknologi MARA, Kedah, 2025)
In an era characterised by unprecedented social justice and environmental sustainability challenges, there is a compelling need for innovative frameworks that foster accountability and transparency. The advent of blockchain technology offers a transformative potential to address these pressing issues by enabling decentralised verification of transactions and activities. Unlike traditional systems, which often suffer from opacity and inefficiencies, blockchain provides an immutable ledger that can track the origins and journeys of products, thereby promoting ethical practices across supply chains. This paper explores the conceptual framework that leverages blockchain for enhanced social and environmental accountability, emphasising its capacity to empower stakeholders and facilitate responsible decision-making. By examining the intersection of technology with governance, this analysis posits that integrating blockchain can bolster accountability and restore public trust in institutions, ultimately contributing to a more equitable and sustainable future.